(untitled) (Scientific journal of the Fergana State University, 2023)
This article talks about taxonomic approaches in forming the scientific and logical outlook of future physics teachers. The levels of development of the logical scientific outlook were analyzed didactically. Teaching physical processes on the basis of taxonomies with the effective use of scientific methodological resources gives the expected result in the formation of the scientific and logical outlook of future physics teachers.